(untitled) (KONFERENSIYA, 2025)
This thesis focus on some effective principles and ways of forming and construction terminology database. Two principles are discussed through thesis:pespective and descriptive way which are considered as main principles not only construction terminoloy but also word forming and systematizing lexic-semantic fields